Divine hiddenness, the melancholic self, and a pandemic spirituality - R. Venter (Acta Theologica)
The COVID-19 pandemic has disrupted societies worldwide and occasioned intense intellectual reflection to make sense of the phenomenon. The state of insecurity has become a new horizon for doing Christian theology, and the new experience makes it inevitable that the spiritual implications be explored. The article attempts to undertake constructive spirituality for a specific historic moment, and to enquire about the contours of a pandemic spirituality. The disciplinary contribution is to be found in the threefold effort to propose a specific naming of God, discern a unique self-understanding, and intimate corresponding practices. Central notions such as hiddenness of God, melancholic self, and practices of everyday life, of lament and of othering are employed coherently to delineate a contextual pandemic spirituality. A multidisciplinary approach is used to interpret these constituent elements.